PENGARUH BOKASHI KOTORAN SAPI TERHADAP BEBERAPA SIFAT FISIK ENTISOL LEMBAH PALU - anang Widjajanto, Uswah Hasanah, Trisno, (AGROTEKBIS, 2016)
This research aimed to determine the effect of adding cow manure bokashi on some physical characteristics of Entisols of Lembah Palu. The research conducted from March to December 2015 at Soil Science Laboratory of Agriculture Faculty of Tadulako University. Soil sample was taken from Sidera village, Sigi Biromaru sub district of Sigi Regency, Central Sulawesi province. The research used a randomize block design with the cow manure bokashi as treatment. The cow manure bokashi was added at various rates i.e. 0%, 5%, 10%, and 15%. Data was analyzed using Analysis of Variance to determine the cow manure effect and Least Significance Ddifferent Test to determine the differences between the treatments. The 15% cow manure bokashi treatment resulted in lowest bulk density (1,28 g cm-3), plasticity index (36,43) and liquid limit (54,17). The same treatment also produced largest porosity (50,75%), field capacity (33,22%) and saturated water (56,38%) contents